1994
DOI: 10.1002/bjs.1800811224
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of experimental acute pancreatitis with a potent platelet-activating factor antagonist

Abstract: The effect of a potent platelet-activating factor (PAF) antagonist, BB-882, on an experimental model of acute pancreatitis induced in male Wistar rats by a technique of microvascular ischaemia was studied. A single intraperitoneal injection of BB-882 (5 mg/kg) 30 min after induction of the disease in 12 animals significantly reduced (P < 0.001) the rise in the level of serum amylase (mean 2477 (range 2100-3280) units/l) compared with that in 12 control animals (mean 3928 (range 2800-5900) units/l) and signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…Table 2 lists measures that have been beneficial when instituted once acute pancreatitis is under way and shows that the common denominator is the control of mast cell pathology [9, 28, 29, 57, 71, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98]. Since impedance to exocytosis in the acinar cell is the detonating event and this is best explained by oxidant-induced interruption to the flow of methyl groups [1], it is logical to regard the resumption of that flow as the reason why re-feeding with methionine [73]or treatment with an analogue of ascorbate [74]– which facilitates the recycling of methyl groups from homocysteine via the folate-vitamin B 12 shuttle – ameliorate in the choline-deficient ethionine-supplemented (CDE) dietary model of severe disease.…”
Section: Formulating a Treatment Strategymentioning
confidence: 99%
“…Table 2 lists measures that have been beneficial when instituted once acute pancreatitis is under way and shows that the common denominator is the control of mast cell pathology [9, 28, 29, 57, 71, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98]. Since impedance to exocytosis in the acinar cell is the detonating event and this is best explained by oxidant-induced interruption to the flow of methyl groups [1], it is logical to regard the resumption of that flow as the reason why re-feeding with methionine [73]or treatment with an analogue of ascorbate [74]– which facilitates the recycling of methyl groups from homocysteine via the folate-vitamin B 12 shuttle – ameliorate in the choline-deficient ethionine-supplemented (CDE) dietary model of severe disease.…”
Section: Formulating a Treatment Strategymentioning
confidence: 99%
“…Treatment of experimental acute pancreatitis with various PAF antagonists has shown a reduction in local and systemic inflammatory changes (68)(69)(70). The only PAF antagonist that has been studied in humans is lexipafant, a molecule that specifically binds to the PAF receptor and which is more potent than other PAF antagonists (71).…”
Section: Platelet Activating Factor (Paf) Antagonistsmentioning
confidence: 99%
“…Progression of the disease and the involvement of PAF have been studied in detail in rat and rabbit models where acute pancreatitis has been induced experimentally using either caerulein administration [24, 30, 62, 65, 66], infusion of bile salts [61, 67, 68], injection of lipopolysaccharides [64], or microvascular ischaemia [69]. These studies have revealed that PAF significantly potentiates pancreatic tissue damage.…”
Section: Mode Of Action Of Paf In Acute Pancreatitismentioning
confidence: 99%
“…Treatment of experimental acute pancreatitis with various PAF antagonists has consistently shown significant local and systemic effects to reduce inflammatory changes (table 2) [24, 25, 30, 62, 66, 67, 69, 79, 80]. In most studies, PAF antagonist administration before or at the time of induction of pancreatitis reduces pancreatic inflammation and oedema, and leads to lower serum levels of pancreatic enzymes.…”
Section: Paf Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation